2000
DOI: 10.1159/000047218
|View full text |Cite
|
Sign up to set email alerts
|

Sun Shades and Eye Size in Birds

Abstract: Visual field width above the head is significantly correlated (rs = 0.92, n = 11, p < 0.001) with eye size in a sample of terrestrial birds that differ in their phylogeny and ecology. These species can be divided into two groups. Smaller-eyed sun-observers (axial length <18 mm) have comprehensive or near comprehensive visual coverage of the celestial hemisphere and are thus unable to avoid viewing the sun. Larger-eyed sun-avoiders (axial length >18 mm) have restricted visual fields and various types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 21 publications
1
42
1
Order By: Relevance
“…We also found that some proposed associations between visual traits were not as strong in emberizid sparrows as in nonPasseriformes. For example, we did not find a relationship between eye size and blind area width, as predicted by the glare hypothesis (Martin and Katzir, 2000). This could be related to our low sample size (i.e.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…We also found that some proposed associations between visual traits were not as strong in emberizid sparrows as in nonPasseriformes. For example, we did not find a relationship between eye size and blind area width, as predicted by the glare hypothesis (Martin and Katzir, 2000). This could be related to our low sample size (i.e.…”
Section: Discussioncontrasting
confidence: 60%
“…glare effects; Koch, 1989). Species with larger eyes can be more prone to glare effects because of larger optical apertures leading to a greater influx of sunlight (Martin and Katzir, 2000). Positioning the sun's image in any blind spot (i.e.…”
Section: Blind Spots and Eye Sizementioning
confidence: 99%
See 1 more Smart Citation
“…ostriches, eagles or albatrosses) have developed sunshade structures (e.g. eyebrows or eye lash-type feathering) and larger blind areas to minimize sunlight glare [49]. Large blind areas reduce the cyclopean field, which might be affordable in large species owing to their lower risk for predation.…”
Section: Box 2 Avian Eyesmentioning
confidence: 99%
“…Large blind areas reduce the cyclopean field, which might be affordable in large species owing to their lower risk for predation. However, species with small eyes generally have smaller blind areas and larger cyclopean fields, because they are not so strongly affected by sunlight and need a wider visual field with which to detect predators [49]. Thus, differences in the size of visual fields seem to be determined by tradeoffs between high acuity, predator vulnerability and sensitivity to light.…”
Section: Box 2 Avian Eyesmentioning
confidence: 99%